Forensic Impact of the Omics Science Involved in the Wound: A Systematic Review - Ros, Aurelia Collados; Bacci, Stefano; Luna, Aurelio; Legaz, Isabel (Frontiers in Medicine, 2022)
Background. In forensic autopsies, examining the wounds is one of the most critical aspects to clarify the causal relationship between the cause of death and the wounds observed on the corpse. However, on many occasions, it is difficult to differentiate antemortem injuries from postmortem injuries, mainly when they occur very close to the moment of death. At present, various studies try to find biomarkers and clarify the molecular mechanisms involved in a wound due to the high variability of conditions in which they occur, thus being one of the most challenging problems in forensic pathology. This review aimed to study the omics data to determine the main lines of investigation emerging in the diagnosis of vital injuries, time of appearance, estimation of the age and vitality of the wound, and its possible contributions to the forensic field. Methods. A systematic review of the human wound concerning forensic science was carried out by following PRISMA guidelines. Results. This study sheds light on the role of omics research during the process of wounding, identifying different cytokines and other inflammatory mediators, as well as cells involved in the specific stage of the wound healing process, show great use in estimating the age of a wound. On the other hand, the expression levels of skin enzymes, proteins, metal ions, and other biomarkers play an essential role in differentiating vital and postmortem wounds. More recent studies have begun to analyze and quantify mRNA from different genes that encode proteins that participate in the inflammation phase of a wound and miRNAs related to various cellular processes. Conclusions. This study sheds light on the role of research in the molecular characterization of vital wounds, heralding a promising future for molecular characterization of wounds in the field of forensic pathology, opening up an important new area of research.